Children with problem-drinking parents in a Swedish national sample: is the risk of harm related to the severity of parental problem drinking?. (15th February 2023) - Ramstedt, Mats; Raninen, Jonas; Larm, Peter; Livingston, Michael
Abstract: Background: The aim of this paper is to examine the link between severity in exposure to parental problem drinking in a Swedish national population sample of children aged 15–16 years. Specifically, we assessed whether the risk of poor health, poor relationships and a problematic school situation increase with severity in exposure to parental problem drinking. Methods: National population survey from 2017 with a representative sample of 5 576 adolescents born in 2001. Logistic regression models were used to estimate odds ratios (ORs) with 95% confidence intervals (95% CIs). A short version of The Children of Alcoholics Screening Test, CAST-6, was used to identify children with problem-drinking parents. Health status, social relations and school situation were assessed by well-established measures. Results: The risk of having poor health, poor school performance and poor social relations increased with severity of parental problem drinking. The risk was lowest among children least severely affected (Crude models ranged from OR: 1.2, 95% CI 1.0–1.4 to OR: 2.2, 95% CI 1.8–2.6) and highest among children most severely affected (Crude models ranges from OR: 1.7, 95% CI 1.3–2.1 to OR: 6.6, 95% CI 5.1–8.6). The risk became lower when adjusting for gender and socioeconomic position but were still higher compared to children without problem-drinking parents. Conclusions: Appropriate screening and intervention programs are necessary for children with problem-drinking parents especially when exposure is severe but also at mild forms of exposure.